2019
DOI: 10.1002/cjce.23478
|View full text |Cite
|
Sign up to set email alerts
|

Single drop breakup in turbulent flow

Abstract: The breakup process of a single drop in homogeneous isotropic turbulence was studied using direct numerical simulations. A diffuse interface free energy lattice Boltzmann method was applied. The detailed visualization of the breakup process confirmed breakup mechanisms previously outlined such as initial, independent, and cascade breakups. High-resolution simulations allowed to visualize another drop breakup mechanism, burst breakup, which occurs when the mother drop has a large volume, and the flow is highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Cristini et al [33] investigated the break-up of droplets which are smaller than the Kolmogorov length of turbulence and are therefore only stressed by laminar shear flows and showed that, in addition to the elongation, the elongation duration is decisive. Komrakova [34] investigated droplet deformation and break-up of droplets exposed to isotropic turbulence and showed that the energy stored as surface energy until breakup can be different. Maniero et al [35] simulated the break-up of droplets in a system-specific high-pressure homogenizer with orifice and generated experimental results very similar to those obtained from the numerical model.…”
Section: Introductionmentioning
confidence: 99%
“…Cristini et al [33] investigated the break-up of droplets which are smaller than the Kolmogorov length of turbulence and are therefore only stressed by laminar shear flows and showed that, in addition to the elongation, the elongation duration is decisive. Komrakova [34] investigated droplet deformation and break-up of droplets exposed to isotropic turbulence and showed that the energy stored as surface energy until breakup can be different. Maniero et al [35] simulated the break-up of droplets in a system-specific high-pressure homogenizer with orifice and generated experimental results very similar to those obtained from the numerical model.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of attention has been dedicated to droplet deformation and breakup in stationary laminar flows [8,13,14,15,16,17,18,19,20,11,10,21,22], but less is known about the dynamics of droplets in homogeneous isotropic turbulent flows, which pose the challenge of solving a multi-physics problem, since the flow properties of the turbulent scales have to be accurately transferred to the scale of the droplet. We can differentiate between two interesting cases for the deformation of droplets in homogeneous and isotropic turbulent flows [23]: On the one hand, there are studies on droplet dynamics on scales larger than the Kolmogorov scale [24,25,26,27,28]. On the other hand, we investigate the dynamics and breakup statistics of sub-Kolmogorov droplets, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This method uses a mesoscopic approach based on the Boltzmann equation to calculate macroscopic quantities (such as velocity and pressure fields). The LBM has proven to be a numerically efficient and accurate method to model fluid flow in complex geometric domains [22,23] and complex fluid modelling, [24,25] including for turbulence [26,27] and heat transfer. [28][29][30] In this method, the flow is calculated by updating the particle distribution functions by collision and streaming steps such as the following:…”
Section: Lattice Boltzmann Methods and Boundary Conditionsmentioning
confidence: 99%